CFD analysis of the performance impact of geometrical shape on volumetric absorbers in a standard cup. (December 2022) - Avila-Marin, Antonio L.; Fernandez-Reche, Jesus; Carballo, Jose Antonio; Carra, Maria Elena; Gianella, Sandro; Ferrari, Luca; Sanchez-Señoran, Daniel
Abstract: The effect of three geometrical parameters of volumetric absorbers in a standard cup –height of the chamfer, the angle of the chamfer and the height of the straight protruding side– on the air temperature at the receiver outlet, the receiver's thermal efficiency and the temperature of the interface between the absorber and the cup are analysed. For the study, 126 different geometrical configurations have been checked in a two-dimensional CFD model. A silicon carbide (SiC) ceramic foam volumetric absorber was selected for the study, and the numerical model adopted includes the simulation of the performance of both the porous media and the cup body. The modelling strategy used was implemented in the commercial CFD code STAR-CCM+ v16.02.009® with a local thermal non-equilibrium model and the Rosseland approximation for the volumetric absorber. The results conclude that different sets of geometrical parameters can produce similar results in terms of air temperature at the cup outlet, thermal efficiency of the system and temperature at the interface between the volumetric absorber and the cup. Emphasizing that the larger the chamfer height the lower the air temperature at the outlet and that the effect of the protruding absorber parameter is influenced by two possible boundary conditions, inlet fluid velocity and wall, and the latter produces the higher air outlet temperature. Highlights: The performance impact of the geometrical shape of a volumetric receiver is analysed. A CFD model was setup, validated and used to check 126 potential geometries. Different sets of geometrical parameters can produce similar performance results.